Re-examining the Myth of Dionysos: A study of Euripides, Ibsen, and Duras - Nasser, Nada Ghazy (AUC Knowledge Fountain, 2014)
The purpose of this thesis is to demonstrate the conflict between the Dionysian, considered as a principle of heightened excess, and social constraint as demonstrated in three different texts from distinct time periods. I will demonstrate how patriarchal and repressive social norms can demolish the sense of individuality that is assumed to be central to society as a whole. The conflict between these two tendencies as expressed in Euripides’s The Bacchae continues to resound in the modern world and explains how a disregard for the Dionysian can lead to destruction and chaos. In this thesis, this conflict, rather than the opposition between Apollo and Dionysos as presented by Nietzsche in The Birth of Tragedy, is discussed in terms of Euripides’s The Bacchae, Henrik Ibsen’s Hedda Gabler, and Marguerite Duras’s Moderato Cantabile. In re-examining the myth of Dionysos, I discuss in conclusion the importance of acknowledging the Dionysian, the danger of over-conforming to standards of constraint, and how the neglect of the Dionysian can lead to destruction, chaos, and disorder.